A case of cardiac amyloidosis in an elderly Japanese patient with amyloidogenic transthyretin Val122Ile variant. Issue 5 (November 2020) - Ono, Ryohei; Takahashi, Hidehisa; Sato, Tetta; Yamazaki, Tatsuro; Hori, Yasuhiko; Fukushima, Kenichi
Abstract: A 76-year-old Japanese man with a history of stomach cancer and chronic atrial fibrillation was referred to our department with left atrial thrombus. He had a history of gastric amyloidosis diagnosed by a pathological specimen of the stomach; however, further examination for amyloidosis was not performed. The patient displayed clinical signs and symptoms of heart failure and echocardiography showed a thick left ventricular wall. Since cardiac amyloidosis was suspected, the patient underwent cardiac magnetic resonance imaging and 99m Tc-pyrophosphate scintigraphy. These results are consistent with transthyretin amyloidosis (ATTR amyloidosis). DNA analysis of transthyretin (TTR) was performed and a heterozygous Val122Ile mutation was identified. Notably, his only son requested the analysis; however, no mutations were noted. ATTR Val122Ile is one of the mutations in TTR that are associated with hereditary amyloidosis, causing severe cardiomyopathy. The prevalence of the ATTR Val122Ile mutation is 3.9% in the African-American population. However, the occurrence of this mutation in Asian populations is very rare. This is the second reported case of the ATTR Val122Ile variant in Japan and the first case tested including familial genes. <Learning objective: Transthyretin amyloidosis (ATTR) Val122Ile variant is rare in Asian people. This is the second case of ATTR Val122Ile variant in Japan and the first case tested including familial genes. This case suggests this mutation is present even in Asian people. It is important to evaluate transthyretin gene mutations even in elderly ATTR cardiac amyloid without apparent family history of amyloidosis. If there is a gene mutation, it is necessary to search for transthyretin mutation within the family members.>